Cliché anthropologists and the interactive probing of aspirations under market expansion - Hizi, Gil (American ethnologist, 2025)
There was a moment in my fieldwork in China when I was prompted to rethink my position in relation to my interlocutors and the values they brought into play. More specifically, I became aware that their image of Western foreigners matched my profile as a wandering anthropologist with incoherent life trajectories. This was so even though, to some degree, they had difficulty translating their image of me into their social reality. Through my research on practices of self‐improvement, I came to see how, in expressing concerns about their personhood and ways of living, my interlocutors moved beyond the telos of business‐driven success. Analytically, I came to better understand how my interaction with them had productively constituted new discursive spaces of the imagination—spaces in which some of our worries were likely to unravel.